Effect of packaging and storage conditions on the pasting and functional properties of pretreated yellow-fleshed cassava flour - Ekeledo, E.; Abass, A.; Muller, J. (Elsevier, 2024)
Cassava is highly susceptible to post harvest physiological deterioration which makes it necessary to initiate processing so as to extend the shelf life. In order to improve and enhance the nutritional characteristics of the processed cassava flour, this research was carried out so as to evaluate the adequate packaging materials and storage conditions necessary for safe storage and good flour quality. Pasting properties of food/flour is an indication of the different applicability of starch-based food ingredients in product development. The effect of packaging materials (cylindric polyvinyl containers and aluminum ziplock pouch bags) on quality attributes of pretreated yellow-fleshed cassava flour (YFCF) samples stored in two storage conditions a (cooling chamber at 5 °C and 30 % relative humidity and; in a climate chamber at 30 °C and 50 % relative humidity) was investigated for 8 weeks. Flour samples from each package type were evaluated for water absorption capacity, pasting and oil absorption capacity fortnightly. The treated initial flour sample before storage-sulfured (BSS) had the highest peak viscosity (891 RVU). The low peak time at the end of storage in non-sulfured flours packed in aluminum pouch bags and stored at 5 °C is an evidence of time and energy saving capacity. The water absorption capacity of non-sulfured flour samples packed in cylindric polyvinyl containers and the sulfured flour sample packed in an aluminum pouch bag at 30 °C increased with storage duration. The aluminum ziplock pouch bags showed excellent storage quality and retained better pasting property. The climatic storage condition revealed better keeping quality. The use of sodium metabisulphite revealed its suitability as a pretreatment tool.